1998
DOI: 10.1051/analusis:1998122
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine interaction with tropical humic substances by Enzyme Linked Immunosorbent Assay

Abstract: Abstract. Enzyme-Linked Immunosorbent Assay (ELISA) has been evaluated by analyzing rich-humic water samples from tropical r ivers. The samples were spiked with atrazine at ppb level. Different pHs (4 to 9) and humic concentrations (2.5 to 40 mg L -1 ) were investigated. The assay performance showed a strong dependence on the pH values and amount of humic matter at low atrazine concentration. F rom all the conditions studied the low pH (pH 4) and high humic substances concentrations (40 mg L to humic acid solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
(14 reference statements)
1
11
0
2
Order By: Relevance
“…Previous work on the use of ELISA's to detect residual agrochemicals in soil samples had shown that humic substances in soil may result in an overestimation of chemical concentrations [20,27,28], and that sample dilution could be used to minimize interference [20]. As a similar type of interference might occur with biomassderived materials such as soluble lignin fragments, supernatants derived from steam pretreated corn stover (SPCS), steam pretreated poplar (SPP), steam pretreated douglas fir (SPDF), and Avicel were assessed for their possible influence on the double-antibody ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work on the use of ELISA's to detect residual agrochemicals in soil samples had shown that humic substances in soil may result in an overestimation of chemical concentrations [20,27,28], and that sample dilution could be used to minimize interference [20]. As a similar type of interference might occur with biomassderived materials such as soluble lignin fragments, supernatants derived from steam pretreated corn stover (SPCS), steam pretreated poplar (SPP), steam pretreated douglas fir (SPDF), and Avicel were assessed for their possible influence on the double-antibody ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate this effect, the calibration curves of BPA were prepared in 10 mM PBS containing 30 mg/L humic acid, which represented organic matters in natural waters at high level40. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work on the use of ELISA’s to detect residual agrochemicals in soil samples had shown that humic substances in soil may result in an overestimation of chemical concentrations [20,27,28], and that sample dilution could be used to minimize interference [20]. As a similar type of interference might occur with biomass-derived materials such as soluble lignin fragments, supernatants derived from steam pretreated corn stover (SPCS), steam pretreated poplar (SPP), steam pretreated douglas fir (SPDF), and Avicel were assessed for their possible influence on the double-antibody ELISA.…”
Section: Resultsmentioning
confidence: 99%